Subcutaneous panniculitis-like T-cell lymphoma, lupus erythematosus profundus, and overlapping cases: molecular characterization through the study of 208 genes. Issue 9 (29th July 2021) - Machan, Salma; Rodríguez, Marta; Alonso-Alonso, Ruth; Manso, Rebeca; Pérez-Buira, Sandra; Borregón, Jennifer; Rodríguez-Peralto, José Luis; Cerroni, Lorenzo; Haro, Rosario; García, Candelaria; García Toro, Enrique; Estrach, Teresa; et al.
Abstract: Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare cytotoxic cutaneous lymphoma. Differential diagnosis with lupus erythematosus panniculitis (LEP) can be challenging and overlapping cases have been described. In this study, we investigate whether gene expression profiling may or not identify markers that can be used to improve our understanding of the disease and to make a precise differential diagnosis. SPTCL, LEP, and overlapping cases were analyzed using a customized NanoString platform including 208 genes related to T-cell differentiation, stromal signatures, oncogenes, and tumor suppressor genes. Gene expression unsupervised analysis of the samples differentiated SPTCL from LEP samples. Most overlapping cases were clustered with LEP cases. Differentially expressed genes were observed when comparing SPTCL with LEP cases; and overlapping with LEP cases. Gene set enrichment analysis recognized gene sets defining each group. In conclusion, SPTCL and LEP have distinctive molecular profiles and the molecular background of overlapping cases more closely resembles LEP.